PENGARUH PROTEAN CAREER ORIENTATION TERHADAP WELL-BEING YANG DIMEDIASI OLEH PSYCHOLOGICAL CAPITAL PADA PEGAWAI NON PNS PEMKO BANDA ACEH - Nanda Mutiara; Hamdi Harmen (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
ABSTRACT:  This study aims to measure the effect of Protean Career Orientation to Well-Being employee’s non PNS Pemko Banda Aceh with Psychological Capital as mediating variable. The sample used in this study were active employee’s totaling 306 respondents. Data collection equipment used in this study was questionnaire. The sampling technique used is Simple Random Sampling. Hierarchical Linear Modelling (HLM) was used as method of analysis to determine the effect of all the variables involved. Based on the result of the HLM analysis indicated that Protean Career Orientation positively influence Well-Being, Protean Career Orientation positively influence Psychological Capital, Psychological Capital influence Well-Being and Psychological mediate the relationship between Protean Career Orientation and Well-Being.